The P2X7R-antagonist AFC-5128 ameliorates chronic experimental autoimmune encephalomyelitis in a preventive and therapeutic paradigm - Hoffrogge, Robert; Karachunskaya, Anna; Heitmann, Neele; Haupeltshofer, Steffen; Pedreiturria, Xiomara; Klöster, Katharina; Bader, Verian; Winklhofer, Konstanze F.; Hamacher, Michael; Klebl, Bert; Gold, Ralf; Dinkel, Klaus; et al. (Frontiers in Immunology, 2025)
BackgroundMultiple sclerosis (MS) is characterized by chronic inflammation driven by central nervous system (CNS)-resident immune cells such as microglia, especially during the progressive phase of the disease. The P2X7 receptor (P2X7R), a risk protein for MS, is ubiquitously expressed on immune cells. AFC-5128, a CNS-penetrating small molecule inhibitor of P2X7R, is a promising agent for the treatment of autoimmune diseases such as MS.MethodsIn vitro, the effects on the calcium influx of primary murine microglia were assessed via Fluo-4 calcium imaging. In vivo, MOG35-55 immunized C57BL/6 mice were treated with AFC-5128, fingolimod (FTY) or vehicle in different treatment paradigms. The mice were scored daily. Microglial marker expression, immune cell phenotyping and serum cytokine analyses were performed via flow cytometry. Immune cell infiltration, demyelination and Iba1+/CD3+ cells were detected in spinal cord cross-sections. The effects of MOG35-55 T-cell restimulation were assessed in vitro.ResultsIn vitro, treatment of primary microglia with 10 µM AFC-5128 reduced the influx of calcium following ATP stimulation (p<0.0001). In vivo, treatment of mice with AFC-5128 led to a reduction in overall EAE scores in acute and chronic EAE, with the best effects using 200 mg/kg body weight AFC-5128 (p<0.0001). Peripheral immune cell subsets (B cells, T cells and macrophages) and serum cytokine levels of chronic EAE mice treated in a therapeutic paradigm were not affected. While the expression of homeostasis markers of microglia in AFC-5128-treated mice was not affected, there was a trend toward lower expression of phagocytosis-associated markers. Late therapeutic treatment with AFC-5128 had only mild effects on chronic EAE.ConclusionThe treatment of EAE mice with AFC-5128 improved acute and chronic EAE in different treatment paradigms, with positive effects on histological markers and slight modulation of microglial marker expression. Mechanistically, calcium influx of microglia was reduced following AFC-5128 treatment, which implies the ability of AFC-5128 to stabilize calcium homeostasis. Therefore, therapeutic inhibition of P2X7R via AFC-5128 has the potential for translation into a treatment of both relapsing and progressive forms of multiple sclerosis.